An environmental-friendly cooling, decontaminating and deodorizing care liquid for automotive interior leather

CN123027072APending Publication Date: 2026-11-03GUANGDONG YIZHI NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611282543.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing automotive interior care products have limited functionality and cannot effectively block near-infrared heat radiation from sunlight, leading to continuous heat accumulation in the interior, accelerating the aging of polymer substrates. Furthermore, their deodorizing effect is short-lived, their storage and usage stability is insufficient, and they are prone to issues such as silicon migration and microbial rancidity.

Method used

This environmentally friendly automotive interior leather care liquid, made with a fully petrochemical system, contains deionized water, anionic emulsification cleaning system, branched tert-carboxylic acid, polyol complex deodorizing components, hydrophilic porous nano-adsorption powder, and near-infrared heat-insulating nano-powder. Through the combination of emulsification cleaning, multi-component synergistic deodorization, near-infrared heat insulation, and fully petrochemical stability, it achieves integrated cleaning, deodorization, and heat insulation and cooling.

Benefits of technology

It achieves integrated cleaning, deodorization, heat insulation and cooling of interior materials. The product is stable under high temperature conditions, avoids silicon migration and microbial rancidity, has antistatic effect, and is suitable for a variety of interior materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses an environmentally-friendly cooling, decontaminating and deodorizing care liquid for automotive interior leather, and belongs to the technical field of automotive interior function maintenance. The care liquid is a water-based full-petrochemical system without organic silicon and biological-based auxiliary agent, and mainly comprises deionized water, an anionic emulsified decontaminating system, a branched tertiary carboxylic acid, an isomeric alkane, a xylose alcohol complex deodorizing component, hydrophilic porous nano-silica, near-infrared heat insulation nano-powder, a pH regulator, a chelating agent and a preservative and bactericide. The mass ratio of the xylose alcohol to the hydrophilic porous nano-silica is 1:2.5-1:3.5, the mass concentration ratio of the hydrophilic porous nano-adsorbing powder to the near-infrared heat insulation nano-powder is 1:(1.2-1.8), and the total mass concentration of solid substances in the system is 0.9%-1.8%. The application integrates cleaning and decontamination, synergistic deodorization, near-infrared heat insulation and cooling, and surface protection, and the treatment is completed by spraying and wiping, and water washing is not needed. The full-petrochemical formula avoids the defects of silicon migration, ash accumulation and whitening, and acidification of biological-based components at high temperature, and meets the long-term storage requirement at 60 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of automotive interior functional care liquid technology, specifically involving an all-petrochemical, silicon-free, and bio-based system automotive interior leather care liquid that combines cleaning, stain removal, heat insulation and cooling, deodorization and protection functions. It is suitable for cleaning, odor control and surface protection of leather and plastic interiors such as passenger cars, yacht interiors, furniture leather goods, and bags. Background Technology

[0002] Car interiors are exposed to high temperatures and sunlight in a closed environment for extended periods. Leather, PVC and other polymer substrates continuously release plasticizers, low-molecular-weight hydrocarbons and aldehydes. Human sweat, grease and dust accumulate, causing unpleasant odors, high temperatures on interior surfaces, and aging and stickiness of the substrate.

[0003] Existing car interior care products have the following shortcomings:

[0004] First, they are limited in function. Traditional cleaning agents only have the ability to remove dirt and do not have the function of heat insulation and cooling; coating and maintenance products focus on polishing and protection, and need to be cleaned before use, but cannot further complete cleaning and maintenance.

[0005] Secondly, the odor removal methods have a short duration of effect. Most products use fragrances to mask odors, but these fragrances evaporate quickly under high temperatures, causing the odor to rebound. Some products add bio-based plant extracts, which are prone to microbial rancidity under high-temperature storage conditions, exacerbating the odor.

[0006] Third, there is insufficient stability during storage and use. Some products contain silicone additives, which can cause silicone migration with long-term use, resulting in oiliness, dust accumulation, and whitening on interior surfaces; alkyl glycoside bio-based surfactants are prone to decomposition and deterioration under high-temperature conditions in vehicles, thus limiting their shelf life.

[0007] Fourth, there is a lack of means to block radiative heat. Existing products cannot block near-infrared heat radiation from sunlight, causing the interior to continuously accumulate heat, accelerating the aging of the polymer substrate, and promoting the release of VOCs from the substrate.

[0008] Currently, there is a lack of technical solutions for automotive interior care liquids that integrate emulsified cleaning, synergistic deodorization of multiple components, near-infrared nano-insulation, and a fully petrochemical stabilization system. Summary of the Invention

[0009] The purpose of this invention is to overcome the shortcomings of the prior art and provide an environmentally friendly automotive interior leather cooling, deodorizing, and cleaning fluid, as well as its preparation method, usage method, and application, to achieve integrated treatment of interior cleaning, deodorization, heat insulation and cooling, and surface protection.

[0010] To achieve the above technical objectives, the present invention adopts the following technical solution:

[0011] An environmentally friendly automotive interior leather cooling, stain-removing, and odor-eliminating care liquid, prepared from the following raw materials by weight:

[0012] The composition includes: 84-87 parts deionized water, 6.8-7.5 parts anion emulsified cleaning system, 0.9-1.1 parts branched tertiary carboxylic acid, 1.8-2.2 parts isoparaffin, 1.2-1.8 parts polyol complex deodorizing component, 0.4-0.6 parts hydrophilic porous nano-adsorbent powder, 0.6-1.0 parts near-infrared heat-insulating nano-powder, 1.1-1.4 parts amine pH adjuster, 0.5-0.6 parts chelating agent, and 0.4-0.5 parts preservative and bactericide.

[0013] The polyol complex deodorizing component is xylitol, and the hydrophilic porous nano-adsorbent powder is hydrophilic nanoporous silica. The mass ratio of xylitol to hydrophilic nanoporous silica is 1:2.5 to 1:3.5.

[0014] The mass concentration ratio of the hydrophilic porous nano-adsorbent powder to the near-infrared heat-insulating nano-powder is 1:(1.2-1.8), and the total mass concentration of solids in the system is 0.9%-1.8%.

[0015] The nursing solution is a fully petrochemical system and does not contain silicone leveling agents, bio-based surfactants, or fragrance masking agents.

[0016] Further, the anionic emulsified detergency system is a fatty alcohol polyoxyethylene ether carboxylate; as a commercial example, a 24% (w / w) aqueous solution of fatty alcohol polyoxyethylene ether carboxylate can be used; the branched tertiary carboxylic acid is neopentanoic acid; the isoalkanes are a mixture of highly branched isoalkanes with a boiling point range of 180–220°C; as a commercial example, a mixture of highly branched isoalkanes (boiling point range: 180–220°C) can be used; the amine pH adjuster is N,N-dimethyl-2-ethanolamine; the chelating agent is disodium ethylenediaminetetraacetate; the preservative and bactericide is 1,2-benzisothiazolin-3-one, with BIT-20 being a commercial example.

[0017] Furthermore, the hydrophilic nanoporous silica has a BET specific surface area of ​​300–600 m² / g, an average pore size of 2–10 nm, a native particle size of 5–50 nm, and a surface hydroxyl content of ≥2 hydroxyl groups / nm²; the near-infrared heat-insulating nanoparticles are selected from cesium tungsten bronze or titanium nitride, preferably titanium nitride, with a native particle size of 10–30 nm, a dispersed particle size D90 ≤ 80 nm in the care solution, and a PDI ≤ 0.15; the titanium nitride powder has a visible light transmittance ≥ 85% and a near-infrared reflectance ≥ 65%.

[0018] Furthermore, the care solution also includes 0.2 to 0.5 parts of a silica-coated modified titanium dioxide core-shell photocatalytic component, used to assist in the decomposition of residual odors and organic pollutants in the interior; the mass ratio of the photocatalytic component to the hydrophilic porous nano-adsorbent powder is 1:(0.5 to 2.0); the hydroxyl groups of the xylitol form intermolecular hydrogen bonds with the silanol groups on the surface of the hydrophilic nanoporous silica to construct an adsorption network, and a polyol solvation layer is formed on the surface of the hydrophilic nanoporous silica; compared with a single powder system without added polyol, the solvation layer improves the capture ability of polar odor molecules by more than 50%.

[0019] Furthermore, the viscosity of the care solution at 25°C is 50–300 mPa·s, and the pH value is 7.5–9.0; after being stored at 60°C for 30 days, it shows no stratification, turbidity, precipitation, or rancid odor; after the care solution solidifies into a film, the visible light transmittance of the film is ≥90%, the haze is ≤5%, and the average reflectance of near-infrared light in the 800–2500 nm wavelength band is ≥60%.

[0020] The present invention also provides a method for preparing the above-mentioned care solution, comprising the following steps:

[0021] S1. Preparation of aqueous substrate: At room temperature, stir deionized water at low speed, add chelating agent and preservative and bactericide in sequence, stir for 5-8 minutes until completely dissolved, and obtain aqueous substrate.

[0022] S2. Constructing an anionic emulsion cleaning system: Add the anionic emulsion cleaning system to the aqueous substrate and stir for 10 minutes to obtain the emulsion cleaning system;

[0023] S3. Neutralization to construct an amphiphilic compatibility system: Add an amine pH adjuster and stir until homogeneous, then add a branched tertiary carboxylic acid, stir at a constant temperature of 45-55℃ for 15 minutes, and neutralize and emulsify to obtain a water-oil compatible system.

[0024] S4. Pre-dispersion of the nano-odor-neutralizing system: Add polyol complex odor-neutralizing components and stir to dissolve. Then add hydrophilic porous nano-adsorbent powder and disperse at high speed for 10 minutes to obtain the odor-neutralizing system.

[0025] S5. Refining and dispersing functional powders: Cool the odor-neutralizing system to below 40°C, add near-infrared heat-insulating nanoparticles, and disperse at high speed for 15 minutes to obtain a functional dispersion.

[0026] S6. Constructing a water-oil microemulsion system: Add isoparaffinic hydrocarbon dropwise under low-speed stirring, and continue stirring for 20 min to obtain the microemulsion system;

[0027] S7. Post-treatment: The microemulsion system is aged at room temperature in a sealed environment for 12-24 hours, and then filtered using a 5-10μm pleated filter cartridge to obtain a stable and transparent care solution.

[0028] The process parameters for each step are matched with the formulation system.

[0029] The present invention also provides a method for applying the above-mentioned care solution: spray the care solution onto the interior surface of the car, let it stand for 20-40 seconds, wipe it with a towel in one direction, and let it air dry to form a film without rinsing with water.

[0030] The present invention also provides the application of the above-mentioned care solution in cleaning, cooling, deodorizing and protecting automotive leather seats, microfiber interiors, PVC plastics, dashboards and door panel interiors.

[0031] The technical solution of this invention mainly includes four functional systems: emulsification and decontamination system, multi-functional synergistic deodorization system, near-infrared heat insulation and cooling system, and all-petrochemical high-temperature stabilization system.

[0032] (1) Emulsified decontamination system

[0033] The fatty alcohol polyoxyethylene ether carboxylate is compounded with neopentanoic acid; neopentanoic acid is neutralized by an amine pH adjuster to generate branched tert-carboxylic acid ammonium salt, which acts as a co-surfactant to expand the micelle solubilization range and has the ability to emulsify and remove sebum, mineral wax and silicone scale. The system is low-foaming and easy to wipe.

[0034] (2) Multi-component synergistic deodorization system

[0035] Xylitol forms hydrogen bonds through its multiple hydroxyl groups, complexing and capturing amine and aldehyde odor molecules. High-surface-area porous silica enriches odor molecules through physical adsorption. Interfacial hydrogen bonds are formed between the silanol hydroxyl groups on the silica surface and the xylitol hydroxyl groups. After spray application and water evaporation, xylitol accumulates in the silica pores via capillary action, creating high-concentration complexed micro-regions within the pores, achieving a synergistic effect of adsorption-enrichment-complexation. Alternatively, silica-coated modified titanium dioxide core-shell particles can be used to degrade VOC molecules under visible light conditions.

[0036] (3) Near-infrared heat insulation and cooling system

[0037] Cesium tungsten bronze or titanium nitride nanoparticles are dispersed in the system, forming a transparent thin layer after application. This layer reflects and absorbs near-infrared heat radiation from sunlight, reducing the surface temperature of interior materials exposed to sunlight. The lower substrate temperature reduces VOC release from the substrate, thus lowering the load on the deodorization system. The powder achieves stable dispersion through coordination and anchoring of anionic surfactant molecules, eliminating the need for silicone dispersants.

[0038] (4) All-petrochemical high-temperature stabilization system

[0039] The formula contains no organosilicon, bio-based surfactants, or fragrances; a buffer system is constructed using neopentanoic acid-dimethylethanolamine; chelating agents shield metal ions; and preservatives and bactericides inhibit microorganisms, ensuring system stability under 60°C storage conditions. A mixture of highly branched isoalkanes (boiling point range: 180–220°C) improves wetting and penetration, accelerates surface drying, and provides moderate antistatic effects after film formation. Detailed Implementation

[0040] Test conditions for this invention:

[0041] The VOC removal rate test was conducted in accordance with the closed static chamber test of GB / T 27630-2011 "Guidelines for Evaluating Air Quality in Passenger Cars"; triethylamine was used as the reference for amine VOCs and formaldehyde was used as the reference for aldehyde VOCs.

[0042] Thermal storage stability: Observe the appearance and odor after being sealed in a 60℃ constant temperature oven for 30 days;

[0043] Cooling test: Black leather substrate, simulated sunlight xenon lamp irradiation, surface temperature was read after steady state, and temperature drop was calculated by comparing with blank substrate;

[0044] Particle size and PDI were determined using dynamic light scattering tests; viscosity was determined using a rotational viscometer at 25°C.

[0045] Example 1 (Preferred Example)

[0046] Raw material weight parts: 86 parts deionized water, 7.2 parts 24% fatty alcohol polyoxyethylene ether carboxylate, 1.0 part neopentanoic acid, 2.0 parts high branched isoalkanes mixture (boiling point range: 180~220℃), 1.5 parts xylitol, 0.5 parts hydrophilic nanoporous silica (xylitol: silica = 3:1), 0.8 parts titanium nitride powder, 1.2 parts N,N-dimethyl-2-ethanolamine, 0.5 parts disodium ethylenediaminetetraacetate, and 0.4 parts BIT-20.

[0047] Prepared according to the preparation method of claim 6; Application: Spray on the interior surface, let stand for 30 seconds, wipe unidirectionally with a microfiber towel, and air dry naturally.

[0048] Performance: Excellent stain removal effect, effectively removing leather grease, sweat stains, and silicone buildup; the product has no irritating odor; under simulated xenon lamp exposure conditions, black leather experiences a steady-state temperature drop of 14-17°C; after 30 days of heat storage at 60°C, the system remains transparent and stable, with no layering or rancid odor; the film forms a transparent, matte, non-greasy film with anti-static properties; 24-hour static testing shows an amine VOC removal rate of ≥68% and an aldehyde VOC removal rate of ≥58%.

[0049] Example 2 (High Transparency Heat Insulation Version)

[0050] In Example 1, titanium nitride was replaced with an equal mass of cesium tungsten bronze, while the other raw materials, processes, and construction methods remained unchanged. The product exhibits lower haze, making it suitable for light-colored interiors; it demonstrates stable near-infrared blocking performance and excellent odor removal capabilities; it cools down by 12–15°C under simulated sun exposure; it remains stable after 30 days of heat storage at 60°C; and it achieves a VOC removal rate of ≥66% for amines and ≥56% for aldehydes.

[0051] Example 3 (Photocatalytic Enhancement Version)

[0052] Based on Example 1, 0.35 parts of silica-coated modified titanium dioxide were added, with the rest remaining unchanged. It continuously degrades and slowly releases VOCs under visible light, improving long-term odor removal; it cools down by 13-16°C under simulated sun exposure; it remains stable after 30 days of heat storage at 60°C; the removal rate of amine VOCs is ≥72%, and the removal rate of aldehyde VOCs is ≥63%.

[0053] Comparative Example 1 (Odor-neutralizing components removed)

[0054] Xylitol and hydrophilic nanoporous silica were omitted; the remaining raw materials and processes were the same as in Example 1. The detergency was normal; the finished product had a slightly irritating odor; it lacked long-term odor suppression capabilities; the removal rate of amine VOCs was ≤20%, and the removal rate of aldehyde VOCs was ≤15%.

[0055] Comparative Example 2 (Insulating Powder Removed)

[0056] Titanium nitride powder was omitted; otherwise, it remained the same as in Example 1. Cleaning and deodorizing performance was normal; it did not have a cooling effect under direct sunlight; amine VOC removal rate was ≥66%, and aldehyde VOC removal rate was ≥56%.

[0057] Comparative Example 3 (replaced with a bio-based surfactant)

[0058] In Example 1, the 24% fatty alcohol polyoxyethylene ether carboxylate was replaced with an equal mass of APG0810, while the rest remained unchanged. After 15 days of heat storage at 60°C, a rancid odor appeared, the system became slightly turbid, and the storage stability decreased.

[0059] Comparative Example 4 (with added silicone leveling agent)

[0060] Based on Example 1, 0.3 parts of silicone leveling agent were added, while the rest remained unchanged; after long-term storage, the film surface is prone to dust accumulation and reduced light transmittance.

[0061] Comparative Example 5 (xylitol only, no porous silica)

[0062] The hydrophilic nanoporous silica was removed, and the xylitol content was adjusted to 2.0 parts; the rest remained the same as in Example 1. After 24 hours of static testing, the removal rate of amine VOCs was approximately 32%, and the removal rate of aldehyde VOCs was approximately 28%.

[0063] Comparative Example 6 (porous silica only, no xylitol)

[0064] Xylitol was removed, and the amount of hydrophilic nanoporous silica was adjusted to 2.0 parts; the rest remained the same as in Example 1. After 24 hours of static testing, the removal rate of amine VOCs was approximately 28%, and the removal rate of aldehyde VOCs was approximately 25%.

[0065] Comparative Example 7 (the ratio of xylitol to silicon dioxide exceeds the specified range)

[0066] The mixture consisted of 0.2 parts xylitol and 1.8 parts hydrophilic nanoporous silica in a mass ratio of 1:9, with the remainder consistent with Example 1. After 24 hours of static testing, the removal rate of amine VOCs was approximately 41%, and the removal rate of aldehyde VOCs was approximately 36%.

[0067] The performance of each embodiment and comparative example is summarized below:

[0068] Group Stain removal and cleaning power Finished product odor Cooling effect of sun exposure 60℃ thermal storage stability Film appearance Amine VOC removal rate Aldehyde VOC removal rate Example 1 Excellent Pure and odorless 14~17℃ 30-day stability Transparent matte finish, non-greasy ≥68% ≥58% Example 2 Excellent Pure and odorless 12~15℃ 30-day stability High transparency and low haze ≥66% ≥56% Example 3 Excellent Pure and odorless 13~16℃ 30-day stability Transparent and flat ≥72% ≥63% Comparative Example 1 Excellent Slightly pungent odor No cooling effect Stablize normal ≤20% ≤15% Comparative Example 2 Excellent Pure and odorless No cooling effect Stablize normal ≥66% ≥56% Comparative Example 3 good The smell of rancidity in the later stages Cooling down is normal Slightly sour and cloudy after 15 days Slight darkening — — Comparative Example 4 Excellent Pure and odorless Cooling down is normal Stablize It easily accumulates dust and turns black. ≥65% ≥55% Comparative Example 5 good Slight odor Cooling down is normal Stablize normal Approximately 32% Approximately 28% Comparative Example 6 good Slight odor Cooling down is normal Stablize normal Approximately 28% Approximately 25% Comparative Example 7 good Slight odor Cooling down is normal Stablize normal Approximately 41% Approximately 36%

[0069] The comparison shows that when xylitol and hydrophilic nanoporous silica are in a ratio range of 1:2.5 to 1:3.5, the synergistic effect of the two is higher than that of the simple superposition of the single components; when the ratio is outside this range, the synergistic effect decreases significantly.

[0070] Beneficial effects

[0071] 1. This invention integrates cleaning and stain removal, synergistic deodorization, near-infrared heat insulation and cooling, and surface protection into one unit. Interior treatment can be completed by spraying and wiping, making construction simple.

[0072] 2. This invention does not use fragrances to mask odors. Instead, it relies on hydrogen bonding, physical adsorption, and optionally photocatalytic degradation to remove odors, reducing odor rebound. Example data shows that the combination of xylitol and hydrophilic porous silica achieves higher VOC removal efficiency than a single component.

[0073] 3. Near-infrared heat-insulating powder forms a transparent protective thin layer, reducing the surface temperature of the interior under sun exposure and slowing down the thermal aging of the polymer substrate; at the same time, the temperature reduction reduces the release of VOCs from the substrate, thus reducing the load on the deodorization system.

[0074] 4. The product adopts a fully petrochemical, silicon-free, and bio-based additive-free formula to avoid silicon migration, dust accumulation, and whitening, as well as the high-temperature rancidity and deterioration of bio-based components. The product meets the requirements for long-term storage at 60℃.

[0075] 5. The product is low-foaming, easy to wipe, requires no rinsing, forms a transparent matte film, has anti-static properties, and is compatible with various interior substrates such as genuine leather, microfiber, PVC, and dashboards. It is suitable for civilian vehicle owners and shop maintenance operations.

Claims

1. An environmentally friendly automotive interior leather cooling, stain-removing, and odor-eliminating care liquid, characterized in that, The care solution is composed of raw materials from all petrochemical sources and does not contain bio-based surfactants or plant-derived fragrances. It is mainly composed of an aqueous base, anionic emulsifying cleaning components, branched tert-carboxylic acid compatible components, isomeric alkane penetrating and fast-drying components, polyol complexing deodorizing components, hydrophilic porous nano-adsorbent powders, near-infrared heat-insulating nano-powders, pH adjusting components, and preservative and stabilizing components. The cleaning solution achieves long-lasting deodorization through the synergistic hydrogen bond adsorption of polyol and hydrophilic porous nano-adsorption powder, cools the interior through near-infrared heat-insulating nano-powder, and constructs a storage-stable cleaning system through the combination of anionic emulsifying components and branched tertiary carboxylic acids. The mass concentration ratio of the hydrophilic porous nano-adsorption powder to the near-infrared heat-insulating nano-powder is 1:(1.2~1.8), and the total mass concentration of solids in the system is 0.9%~1.8%.

2. The environmentally friendly automotive interior leather cooling, stain-removing, and odor-eliminating care liquid according to claim 1, characterized in that, By weight, the following raw materials are included: 84-87 parts deionized water, 6.8-7.5 parts fatty alcohol polyoxyethylene ether carboxylate, 0.9-1.1 parts neopentanoic acid, 1.8-2.2 parts high branched isoalkanes with a boiling point of 180-220℃, 1.2-1.8 parts xylitol, 0.4-0.6 parts hydrophilic nanoporous silica, 0.6-1.0 parts near-infrared heat-insulating nanoparticles, 1.1-1.4 parts N,N-dimethyl-2-ethanolamine, 0.5-0.6 parts disodium ethylenediaminetetraacetate, and 0.4-0.5 parts 1,2-benzisothiazolin-3-one; The mass ratio of xylitol to hydrophilic nanoporous silica is 1:2.5 to 1:3.

5.

3. The environmentally friendly automotive interior leather cooling, stain-removing, and odor-eliminating care liquid according to claim 2, characterized in that, The hydrophilic nanoporous silica has a BET specific surface area of ​​300-600 m² / g, an average pore size of 2-10 nm, a primary particle size of 5-50 nm, and a surface hydroxyl content of ≥2 hydroxyl groups / nm². The near-infrared heat-insulating nanoparticles are cesium tungsten bronze or titanium nitride, preferably titanium nitride; their original particle size is 10-30 nm, and their dispersed particle size in the system is D90≤80 nm, PDI≤0.

15.

4. The environmentally friendly automotive interior leather cooling, stain-removing, and odor-eliminating care liquid according to claim 1, characterized in that, The care solution also includes a silica-coated modified titanium dioxide core-shell photocatalytic component, used to assist in the decomposition of residual odors and organic pollutants in the interior; The mass ratio of the photocatalytic component to the hydrophilic porous nano-adsorbent powder is 1:(0.5-2.0). The hydroxyl groups of xylitol form intermolecular hydrogen bonds with the silanol groups on the surface of hydrophilic nanoporous silica, constructing an adsorption network and forming a polyol solvation layer on the surface of hydrophilic nanoporous silica. Compared with a single powder system without added polyol, this solvation layer improves the ability to capture polar odor molecules by more than 50%.

5. The environmentally friendly automotive interior leather cooling, stain-removing, and odor-eliminating care liquid according to any one of claims 1-4, characterized in that, The nursing solution has a viscosity of 50-300 mPa·s at 25°C and a pH value of 7.5-9.0; after being stored at 60°C for 30 days, it shows no stratification, turbidity, precipitation, or rancid odor. After the nursing solution is cured into a film, the visible light transmittance of the film is ≥90%, the haze is ≤5%, and the average reflectance of near-infrared light in the 800-2500nm band is ≥60%.

6. A method for preparing an environmentally friendly automotive interior leather cooling, stain-removing, and odor-eliminating care liquid, characterized in that, The preparation of the nursing solution according to any one of claims 1-5 comprises the following steps: S1. Preparation of aqueous substrate: Under normal temperature conditions, dissolve the chelating agent and the preservative and bactericide in deionized water in sequence. S2. Construct an anionic emulsion cleaning system: Add anionic emulsion cleaning components and stir until evenly mixed; S3, Neutralization to construct an amphiphilic compatibility system: Add an amine pH adjuster, then add a branched tertiary carboxylic acid, and neutralize and compatibility under medium-temperature isothermal conditions; S4. Pre-dispersion of the nano-odor-neutralizing system: Add polyol complex odor-neutralizing components and hydrophilic porous nano-adsorbent powder for high-speed dispersion; S5. Refining and dispersing functional powders: Near-infrared heat-insulating nanoparticles are added after cooling to refine and disperse them. S6. Constructing a water-oil microemulsion system: Add isoparaffins at low speed and combine to form a water-oil microemulsion system; S7. Post-treatment: Sealed aging, followed by precision filtration to obtain a stable and transparent care solution; The process parameters for each step are matched with the formulation system.

7. A no-rinse application process for the nursing solution according to any one of claims 1-5, characterized in that, Spray the care solution evenly onto the car interior trim, let it sit for 20-40 seconds to wet, then wipe and polish. Allow it to air dry naturally to form a film. No rinsing with water is required throughout the process, achieving a one-stop solution for cleaning, cooling, deodorizing, and protection.

8. A multi-functional protective application for interior interiors, characterized in that, The care solution described in any one of claims 1-5 is applied to automotive leather, microfiber, PVC, dashboard, door panel plastics and leather interiors for rinse-free cleaning, near-infrared cooling, adsorption and deodorization, and weather protection.

9. An environmentally friendly car interior leather care kit, characterized in that, Includes individually packaged first and second components; The first component is the remaining liquid components in the nursing solution according to any one of claims 1-5, excluding near-infrared heat-insulating nanoparticles and hydrophilic porous nano-adsorbents. The second component is a pre-dispersion slurry of near-infrared heat-insulating nanoparticles and hydrophilic porous nano-adsorption powders; When using, mix the first component and the second component evenly at a mass ratio of (30-40):1 before spraying.

10. The environmentally friendly automotive interior leather care kit according to claim 9, characterized in that, The second component also contains 0.5% to 2.0% polyethylene glycol or polyvinylpyrrolidone as a dispersion stabilizing agent, accounting for 0.5% to 2.0% of the total mass of the second component.